3(3x+-2)=4+-6x

Simple and best practice solution for 3(3x+-2)=4+-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+-2)=4+-6x equation:


Simplifying
3(3x + -2) = 4 + -6x

Reorder the terms:
3(-2 + 3x) = 4 + -6x
(-2 * 3 + 3x * 3) = 4 + -6x
(-6 + 9x) = 4 + -6x

Solving
-6 + 9x = 4 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-6 + 9x + 6x = 4 + -6x + 6x

Combine like terms: 9x + 6x = 15x
-6 + 15x = 4 + -6x + 6x

Combine like terms: -6x + 6x = 0
-6 + 15x = 4 + 0
-6 + 15x = 4

Add '6' to each side of the equation.
-6 + 6 + 15x = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 15x = 4 + 6
15x = 4 + 6

Combine like terms: 4 + 6 = 10
15x = 10

Divide each side by '15'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| Y=-4.8(0)+1.2 | | 2(3x+-2)=4+-6x | | 150m-125m+38200=40400-175m | | 6m-2=m+3 | | (54b-27ab)= | | 2x^2-20=8 | | 3n+8=92 | | 20y=25y^2 | | 5x-11=8x+12 | | 4x-20.65=6.7 | | 3x+y=7xy | | 0.5x+0.1*5x=62.15 | | X^2=11x-56 | | 0.5x+0.1(5x)=62.15 | | 4x-20.65=20.1 | | -6f-9f=15 | | 15c+1c+21c= | | 61h=9.3-3.2h | | 7y-10y+6=9 | | x^3-4x+x+6=0 | | 7k-5=19 | | cot^2x=-2 | | 2(4x-3)+10=-6(-x+1)-12 | | 1600-320x+12x^2=0 | | 0.7x-0.6x-9=6 | | 32=1.60x | | K-16=2 | | 2(x+3)+7=9 | | R+R^2=24 | | (3m+8)3+m= | | X^2-31x-30=0 | | 2(9x-1)=-3(5-9x)+2 |

Equations solver categories